The Influence of Viral Marketing and Atmosphere on Purchase Decisions with FOMO as Moderation in Coffee Shops - Made Setini; Ni Putu Ita Puspa Yanti; Ni Luh Putu Indiani (Asean International Journal of Business, 2026)
Purpose – This paper seeks to examine the influence of menu variations on Generation Z customer loyalty in coffee shops in Denpasar City, with customer satisfaction as a mediating variable and social media marketing as a moderating variable. Methodology/approach – A quantitative explanatory approach was applied using questionnaire data collected from 175 Generation Z respondents who frequently visit coffee shops in Denpasar. The data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect relationships among menu variations, customer satisfaction, social media marketing, and loyalty. Findings – The results indicate that menu variations have a positive and significant effect on both customer loyalty and customer satisfaction. However, customer satisfaction does not significantly influence loyalty and fails to mediate the relationship between menu variations and loyalty. Furthermore, social media marketing plays a quasi-moderating role, strengthening the effect of menu variations on loyalty while also directly influencing loyalty. These findings suggest that Generation Z loyalty is more strongly driven by innovative product experiences and digital engagement rather than satisfaction alone. Novelty/value – This study contributes to the growing literature on Generation Z consumer behavior in the coffee shop industry by highlighting the importance of continuous menu innovation supported by effective social media marketing strategies to build and maintain long-term customer loyalty.